Rapidly Changing Marketing Channels of FMCG Companies - A Case Study of Patanjali Ayurved Limited - Yadav, S. K. (Journal of Commerce and Trade, 2017)
Fast Moving Consumer Goods (FMCG) goods are popularly named as consumer packaged goods. Items in this category include all consumables people buy at regular intervals. The most common in the list are toilet soaps, detergents, shampoos, toothpaste, shaving products, shoe polish, packaged foodstuff, and household accessories and extends to certain electronic goods. These items are meant for daily of frequent consumption and have a high return.